2021
DOI: 10.1111/jhn.12909
|View full text |Cite
|
Sign up to set email alerts
|

Use of neck circumference as a predictor of cardiovascular risk in chronic kidney patients undergoing haemodialysis who are candidates for transplantation

Abstract: Introduction Patients undergoing haemodialysis are at great cardiovascular risk. Neck circumference (NC) is a simple and low‐cost measure for estimating this risk precociously. The present study aimed to evaluate whether the cardiovascular risk obtained by NC is associated with the main cardiometabolic risk factors in patients on haemodialysis treatment who are on a waiting list for transplantation. Methods A cross‐sectional study was conducted including 96 patients in a single transplantation centre. Socio‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Regarding NC, this has been recognized as a parameter indicating cardiometabolic diseases [23], which has been promising in evaluating the risk of kidney failure [10]. Medeiros et al [24] showed that NC is associated with cardiometabolic risk factors in kidney failure patients on hemodialysis on a transplant waiting list, and Liu et al [25] found an association between NC and CKD indicators for patients at high cardiometabolic risk. In addition, the study of Hsiao et al [17] showed evidence that NC and albuminuria are determining factors for a precise and successful estimate of the glomerular filtration rate in patients at high cardiovascular risk, suggesting that NC should potentially be investigated in more studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding NC, this has been recognized as a parameter indicating cardiometabolic diseases [23], which has been promising in evaluating the risk of kidney failure [10]. Medeiros et al [24] showed that NC is associated with cardiometabolic risk factors in kidney failure patients on hemodialysis on a transplant waiting list, and Liu et al [25] found an association between NC and CKD indicators for patients at high cardiometabolic risk. In addition, the study of Hsiao et al [17] showed evidence that NC and albuminuria are determining factors for a precise and successful estimate of the glomerular filtration rate in patients at high cardiovascular risk, suggesting that NC should potentially be investigated in more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Neck circumference has been considered an important marker of subcutaneous fat deposits in the upper body and a simple screening tool for identifying individuals with obesity [27,28]. In this sense, increased values suggest a greater risk for cardiovascular diseases in the population in general and in kidney failure patients [9,24]. The fatty acids released from subcutaneous fat in the upper body can result in oxidative stress and vascular lesions, causing an increased risk for cardiovascular diseases in individuals with higher NC [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although malnutrition appears to play a role in the development of cardiovascular disease, which is proposed as the malnutritioninflammation-atherosclerosis syndrome, 4 the association between malnutrition and MACE has not been consistently demonstrated. [32][33][34][35] Other complex mechanisms can result in MACE, especially in patients receiving chronic haemodialysis; thus, various parameters have been proposed to evaluate the risk of MACE for this disease populations. [36][37][38] On the other hand, the distinction may result from the technique used for assessing malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early prediction of cardiometabolic risk is extremely important. Cardiometabolic risk factors contain high body mass index (BMI), raised low-density lipoprotein cholesterol (LDL), reduced high-density lipoprotein cholesterol (HDL), ascended total cholesterol (TC), raised triglyceride (TG), increased systolic blood pressure (SBP) and diastolic blood pressure (DBP), and elevated fasting glucose [ 7 ], all of which are associated with an increased risk of cardiovascular disease. One study showed that cardiometabolic risk was associated with abnormal glomerular filtration rate in the general population [ 8 ], and there was a significant association between cardiovascular disease risk and the severity of CKD [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%